2002
DOI: 10.1002/syn.10128
|View full text |Cite
|
Sign up to set email alerts
|

Brain imaging of18F‐fallypride in normal volunteers: Blood analysis, distribution, test‐retest studies, and preliminary assessment of sensitivity to aging effects on dopamine D‐2/D‐3 receptors

Abstract: Human studies of dopamine D2/D3 receptors using 18F-fallypride-PET in normal volunteers were performed to evaluate brain distribution in striatal and extrastriatal regions, evaluate metabolites in blood plasma, establish PET imaging protocol for this new radiotracer, evaluate graphical methods of analysis to quantitate D2/D3 receptors, and assess the ability of 18F-fallypride to measure changes in D2/D3 receptors with aging as a model. Subjects (6; 21-63 years) had a PET scan on a Siemens HR+ scanner with 18F-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
205
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(228 citation statements)
references
References 52 publications
21
205
1
1
Order By: Relevance
“…However, the low D 2 receptor density in the cortex in conjunction with the use of a normal control group for the baseline condition contributes to the comparatively high variability in our data for these regions. Nevertheless, Mukherjee et al (2002) found a test-retest variability of less than 10% both for striatal and temporal cortical regions, supporting the view that D 2 receptors can be reliably quantified with [ 18 F]fallypride even in brain regions with a low D 2 density (Mukherjee et al, 2002).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…However, the low D 2 receptor density in the cortex in conjunction with the use of a normal control group for the baseline condition contributes to the comparatively high variability in our data for these regions. Nevertheless, Mukherjee et al (2002) found a test-retest variability of less than 10% both for striatal and temporal cortical regions, supporting the view that D 2 receptors can be reliably quantified with [ 18 F]fallypride even in brain regions with a low D 2 density (Mukherjee et al, 2002).…”
Section: Discussionsupporting
confidence: 58%
“…It has been consistently demonstrated in human studies that a dynamic scan of 180 min duration allows for establishment of a transient equilibrium both in extrastriatal and striatal brain regions (Mukherjee et al, 2002;Siessmeier et al, 2005). Furthermore, Mukherjee et al (2002) have shown that the test-retest variability in all brain regions is below 10%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14] Moreover, a recent study using diffusion-weighted magnetic resonance imaging and PET found that connectivity-based subdivision of human striatum improved the evaluation of regional differences in DA transmission, supporting an association between striatal DA release and cortical connectivity. 35 36,37 In the current study, cortical VAR and ICC values were good to moderate, ranging from 6.1%, 0.79 (temporal cortex) to 13.1%, 0.67 (superior frontal gyrus). This is clearly superior to previous results by Stokes et al 11 and comparable to test-retest parameters obtained with high-affinity ligands.…”
Section: Discussionsupporting
confidence: 55%
“…One striking observation of our study was the conspicuously high level of [ 11 C]-( + )-PHNO binding in GP, a region that does not stand out as having a particularly high D 2 -receptor density in vitro and that has been scarcely studied using PET or SPECT. (Farde et al, 1997;Fujita et al, 1999;Mukherjee et al, 2002) but did not report on the visualization of GP in vivo. Only one PET study, using [ 11 C]FLB457 in human, clearly identified GP as a region with high D 2/3 binding, with a binding only slightly less than that measured in caudate-putamen (Okubo et al, 1999).…”
Section: Discussionmentioning
confidence: 99%